PERFORMANCE EVALUATION FOR STRENGTH OF M30 DESIGN MIX CONCRETE WITH PARTIAL RPLACEMENT OF CONVENTIONAL INGREDIENTS IN CEMENT AND FINE AGGREGATE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Concrete has been a major construction material for centuries. Yet concrete construction so far is mainly based on the use of virgin natural resources. Cement and aggregate, which are the majority significant component utilized in concrete creation, are the crucial resources desirable for construction industry. This inevitably led to a continuous and growing demand of natural resources utilized for their production. With this the concrete protection becomes an important issue; hence it has to be replaced with other materials. The present paper focuses on investigating characteristics of M30 concrete with limited substitute of cement with Municipal solid waste incineration (MSWI) ash and sand with the stone dust (crusher sand). The cubes and cylinders are tested for compression, flexure and tensile strengths. It is found that by the limited substitution of cement with MSWI ash and sand with Stone dust helped in betterment of the strength of the concrete significantly compared to ordinary mix concrete.